ENGLISH LITERACY MANAGEMENT AT SMPI AL ABIDIN SURAKARTA - Fithriyah Nurul Hidayati (JURNAL AL-TANZIM, 2021)
This study aims to analyze the implementation of school management to improve students' English literacy at SMP Islam Al Abidin Surakarta. This study uses a qualitative approach with a phenomenological method. The process of seeking and finding information related to English literacy improvement management is carried out through the 5W + 1H process. The study results showed that the implemented school management consisted of steps that supported English literacy starting from planning, organizing, implementing and evaluating activities. 1) The planning steps is related to determining goals, objectives, designing literacy activity programs, 2) organizing the resource, 3) implementing related to English literacy is through the following programs: (a) English Development Program, such as: English Camp, English Festival, Saturday Performance, Every day is English day, and Five Minutes Presentation (b) Literacy Programs, such as: Reading, Listening, Speaking Time and 4) controlling of implementing English literacy.